Carrier relaxation dynamics in defect states of epitaxial GaN/AlN/Si using ultrafast transient absorption spectroscopy. Issue 102 (5th October 2015) - Dugar, Palak; Kumar, Mahesh; T. C., Shibin Krishna; Aggarwal, Neha; Gupta, Govind
Abstract : Carrier relaxation dynamics through the defect levels in an epitaxial GaN/AlN/Si have been analysed on the femto–picosecond timescale, using ultrafast-transient absorption spectroscopy. Abstract : The relaxation dynamics of the carriers through the defect levels in an epitaxial GaN film grown with an AlN buffer layer on Si has been performed on the femto–picosecond timescale, using ultrafast transient absorption spectroscopy (UFTS). The sample was pumped above and below the band gap and probed with a white light continuum (480–800 nm). A combination of bi and triple exponential decay functions at different probe wavelengths were used to fit the kinetic profile of the carriers in the defect continuum. Based on the UFTS measurements, a model is proposed which explains the dynamics in the shallow traps and deep level defects. Furthermore, to determine the role of the lattice in the relaxation dynamics, the experiment was conducted at a low lattice temperature of 4.2 K. The relaxation constants from the UFTS measurements confirm not only the presence of shallow and deep level defects but also the involvement of phonons in one of the relaxation processes.